Integrating Ecocriticality and Critical Path Method for Enhancing Time Efficiency and Reduce Environmental Impact - Muin, Suriati Abd.; Watono; Putri, Cindy Melanie; Al-Asfahany, Salsabila (UKaRsT, 2025)
Time efficiency and environmental responsibility are increasingly recognized as essential dimensions of modern construction management. However, most scheduling studies using the Critical Path Method (CPM) primarily focus on duration optimization, whereas the ecological impacts associated with critical activities remain overlooked. This study aims to combine CPM with an ecocriticality-based assessment of time efficiency by considering the associated ecological burden. A case study was conducted on the construction of the Integrated Laboratory and Landscape Building at the Habibie Institute of Technology in Parepare, Indonesia. Project scheduling data, cost budget documents, and material volume records were analyzed to identify critical path activities and quantify their ecological burden. Ecocriticality Index (IE) was assessed based on four weighted environmental parameters, such as material consumption, solid waste generation, reuse potential, and embodied emissions. The results show that the integration of CPM with Ecocriticality provides a more comprehensive scheduling basis by simultaneously combining time efficiency and ecological burden. Its application resulted in an optimal duration of 1 week faster and identified floor and foundation elements with the highest environmental impact and located on the critical path. This integration also produced three priority schemes that can be used as a basis for selecting intervention strategies. These findings confirm that project acceleration decisions cannot be separated from ecological assessments. The integration of CPM and Ecocriticality provides an approach that can be applied to various projects to improve time efficiency while reducing environmental impacts and supporting sustainable construction.